Impact of frontline demonstrations on the yield and economics of castor in Saurashtra region of Gujarat under climate change conditions: IMPACT OF FLDs ON YIELD AND ECONOMICS OF CASTOR IN SAURASHTRA REGION OF GUJARAT - P M VAGHASIA; K L DOBARIYA (Journal of Oilseeds Research, 2018)
Sixty five frontline demonstrations (FLDs) were organized on farmers’ fields to demonstrate the impact of improved technology on castor productivity in Saurashtra region of Gujarat state during the years 2011-12 to 2015-16 under irrigated conditions to ascertain the yield gaps between improved technology (IT) and farmer’s practice (FP) in castor crop. The productivity and economic returns of castor crop in improved technologies were calculated and compared with the corresponding farmer’s practices (local checks). In the FLDs, the results revealed that seed yield (3640 kg/ha) of improved technology was higher as compared to farmers’ practice (3148 kg/ha). Higher gross returns, net returns and benefit cost ratio were recorded in FLD plots as compared to farmers’ practice plots. The average technology gap, extension gap and technology index were 3360 kg/ha, 492 kg/ha and 94 per cent, respectively in FLD plots as compared to farmers’ practice plots. Each year, extension gap was lower than technology gap indicating the need to educate farmers in adoption of improved technologies. It is suggested that location-specific approaches would be needed to bridge the productivity gap of castor crop in the region.